Development of Animated Video-Based Learning Media Using the Animaker Application on Theme 7 Sub-theme 1 Class V SDN 101765 Bandar Setia - Robenhart Tamba; Vinka Nova Tutiona Simanjuntak (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to prove the effectiveness of Animaker-based animation video learning media products on theme 7 sub-themes 1 learning 1, 2 and 3 Class V SDN 101765 Bandar Setia. The type of research used in this research is research and development or Research and Development (R&D) with the ADDIE development model. This research and development was carried out at SDN 101765 Bandar Setia which is located on Jln.Perjuangan Bandar Klippa, Kec.Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The subjects of this research and development were 24 students of class V at SDN 101765 Bandar Setia and also teachers of class V (Five). The object of this research is the development of animation-based video-based media on theme 7 sub-themes 1 of learning 1,2, and 3. The results of the study show that proving that animation-based video learning media using animakers has succeeded in increasing student learning outcomes and increasing student learning interest, as well as video education with animation is positive enough to be used in learning and meets the criteria of